2012
DOI: 10.1192/pb.bp.112.039727
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular health of young people with severe mental illness: addressing an epidemic within an epidemic

Abstract: SummaryFor young people with emerging psychosis, early weight gain and its potential cardiac and metabolic consequences amplify worrying UK public health trends for young people in general. This paper will argue that if clinicians dismiss these changes as of secondary concern in psychiatric treatment for their young patients, they may be inadvertently condoning a first critical step on a path towards physical health inequalities. Greater recognition is needed for this patient population in their 20s and 30s, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…They need to be provided clear and consistent information that enables them to understand and weigh up the benefits and risks of psychotropic treatment, so that treatment decisions can be negotiated and fit with their individual aspirations and values (Bailey et al . ; Murphy et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They need to be provided clear and consistent information that enables them to understand and weigh up the benefits and risks of psychotropic treatment, so that treatment decisions can be negotiated and fit with their individual aspirations and values (Bailey et al . ; Murphy et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Bailey et al . () emphasize the particular concern that significant weight gain/obesity in this group can trigger the emergence of other cardiometabolic disturbances.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although antipsychotic medication is helpful for some, it is ineffective for others and is associated with significant adverse effects that may outweigh perceived benefits and lead to discontinuation (5,6). It has been suggested that there is an excessive reliance on antipsychotic medication in the treatment of schizophrenia and related disorders and that there is "little or no choice offered to service users who meet criteria for such diagnoses, despite policies that actively promote patient-led care, collaborative decision-making and provision of choice" (7).…”
mentioning
confidence: 99%